Problematika Globalisasi Hukum di Indonesia: Dari Perjanjian Internasional Menjadi Hukum Nasional - Zul Fadli (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
In our time, globalization can not be avoided, technology and economic are themain factors. Because people become more and more connected, the globalization of lawis imminent. Through interntional egreement, the globalization of law find its power to be enforced. Nevertheless, this sircumstances alsocreated new challenges, especially on legal aspect. Legal transplantation can not be easily pursued because the characteristic of legal systemof every nation is varied.